Enhancing natural killer cell function with gp41-targeting bispecific antibodies to combat HIV infection - Ramadoss, Nitya S; Zhao, Nancy Q; Richardson, Barbra A; Grant, Philip M; Kim, Peter S; Blish, Catherine A (bioRxiv, 2019)
Objective(s): To develop and evaluate the activity of bispecific antibodies (bsAbs) to enhance NK cell antibody-dependent cellular cytotoxicity (ADCC) against HIV-infected cells. Design: These bsAbs are based on patient-derived antibodies targeting the conserved gp41 stump of HIV Env, and also incorporate a high affinity scFv targeting the activating receptor CD16 on NK cells. Overall, we expect the bsAbs to provide increased affinity and avidity over their corresponding monoclonal antibodies, allowing for improved ADCC activity against Env-expressing target cells. Methods: bsAbs and their corresponding mAbs were expressed in 293T cells and purified. The binding of bsAbs and mAbs to their intended targets was determined using Bio-Layer Interferometry, as well as flow cytometry-based binding assays on in vitro infected cells. The ability of these bsAbs to improve NK cell activity against HIV-infected cells was tested using in vitro co-culture assays, using flow cytometry and calcein release to analyze NK cell degranulation and target cell killing, respectively. Results: The bsAbs bound gp41 with similar affinity to their corresponding mAbs, and had increased affinity for CD16. The bsAbs also bound to primary CD4 T cells infected in vitro with two different strains of HIV. In addition, the bsAbs induce increased NK cell degranulation and killing of autologous HIV-infected CD4 T cells. Conclusions: These bsAbs may provide a promising strategy to improve NK-mediated immune targeting of infected cells during HIV infection.